Hybrid spatial‐spectral MoM analysis of microstrip structures. (28th December 2015) - Essid, Chaker; Ben Salah, M. Bassem; Samet, Abdelaziz
Summary: In this paper, a new hybrid method formulation to resolve the mixed potential integral equation in an efficient and a fast approach, which is based on a simultaneous formulation in both spatial and spectral domains, is proposed. The entries of the method of moments matrix are then given by the sum of two integrals. The first one is expressed in the spatial domain. This part is analytically evaluated after a development in Taylor series of the exponential terms in the function to integrate. The integrals expressed in the spectral domain have a finite range, and they are calculated using numerical integration. Then the convergence problem is avoided in this approach. A good agreement between the simulated and measured results has been achieved. Copyright © 2015 John Wiley & Sons, Ltd.